2015
DOI: 10.1007/s11419-015-0265-x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of 37 synthetic cannabinoid metabolites in human urine by liquid chromatography-tandem mass spectrometry

Abstract: Despite efforts by legal authorities to control the abuse of synthetic cannabinoids, new derivatives have continually emerged on the market to circumvent regulations, and its abuse has become a threat to public health. Thus, development of analytical methods for confirming drug intake in biological fluids is essential to ensure effective drug control and to address further drug intoxication cases. Herein, a sensitive and reliable liquid chromatography-tandem mass spectrometry method was established and validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
2
33
1
Order By: Relevance
“…Concentrations of M1 and M11 in each sample were determined after 7, 14, 21, and 28 days by LC–MS/MS. Metabolites M1 and M11 in urine specimens were found to be relatively stable under all conditions examined (ranged from 70.9 to 124%), as was also reported in another article showing excellent stabilities of synthetic cannabinoid metabolites in human urine …”
Section: Resultssupporting
confidence: 84%
“…Concentrations of M1 and M11 in each sample were determined after 7, 14, 21, and 28 days by LC–MS/MS. Metabolites M1 and M11 in urine specimens were found to be relatively stable under all conditions examined (ranged from 70.9 to 124%), as was also reported in another article showing excellent stabilities of synthetic cannabinoid metabolites in human urine …”
Section: Resultssupporting
confidence: 84%
“…In our previous study [16], it was impossible to detect unchanged AB-CHMINACA from the urine specimen of the same individual. Very recently, Jang et al [17] reported the levels of metabolites of synthetic cannabinoids having aliphatic side chain structures (pentyl, butyl and hexyl aliphatic chains) in authentic urine specimens; their levels ranged from 0.3 to 420 ng/ml. However, the level of 420 ng/ml was exceptional; all levels (20 level data) except the highest one were not greater than 38 ng/ml.…”
Section: Concentrations Of the Metabolites M1 And M3 In An Authentic mentioning
confidence: 99%
“…As reported by our group [15,16], the unchanged synthetic cannabinoids could be detected from solid tissues, but not from urine specimens. To disclose the abuse of synthetic cannabinoid(s) using urine specimens, it is essential to identify and quantify the predominant metabolite(s) in human urine [17]. As to AB-CHMINACA, only one report [18] has appeared; they studied in vitro metabolism of AB-CHMINACA using human liver microsomes, followed by the estimation of metabolites by liquid chromatography-time-of-flig ht-mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods can only identify the compounds they are designed for, and updates are not easily performed. A number of quantitative screening methods in urine by LC–MS/MS have previously been published . High resolution mass spectrometry (HRMS) with quadrupole time of flight (QTOF) instrumentation that acquires full spectrum data is not limited by scan/dwell times, and introducing new masses/formulas to the method will not affect the detection of the previously included ones.…”
Section: Introductionmentioning
confidence: 99%